The effect of hydrothermal conditions on the formation of productivity of the facultative barley variety ‘Marusya’ in the southern part of the Rostov region - A. S. Popov; G. V. Ovsyannikova; A. A. Sukharev; A. A. Dontsova; D. P. Dontsov; G. M. Zelenskaya; I. V. Fetyukhin; О. S. Lesnykh (Зерновое хозяйство России)
In the cultivation regions with unstable moisture there are fluctuations in grain crop productivity, which is mainly determined by the definite hydrothermal conditions. The purpose of the current study was to determine the effect of hydrothermal conditions on the formation of barley productivity during autumn and spring sowing periods in the southern part of the Rostov region. When conducting the trial, barley plants experienced a lack of air humidity and were insufficiently provided with precipitation, both in autumn and spring sowing periods, and the coefficient of moisture supply for barley crops was 0.53 and 0.45, respectively. There was found that the longest vegetation period of 235 days was observed during sowing on September 10, when the sum of positive temperatures was also the highest, 2010.4 °C. In the spring sowing periods, these indicators were the smallest: the vegetation period was 83 and 92 days, the sum of positive temperatures was 1555.2 and 1579.3 °C, respectively. There was established that for productivity formation (6.38 t/ha) in autumn sowing, the total moisture consumption of the facultative barley variety ‘Marusya’ was 308.5 mm per 1 ha, and the total moisture consumption per 1 ton of grain was 483.5 m3 on average for 2018-2020. In the total consumption of moisture, precipitation was 95%, and the share of soil moisture was 5%. When sowing in the spring, the variety ‘Marusya’ produced 4.26 t/ha and consumed 211.4 mm of moisture per hectare, and the total moisture consumption per 1 ton of grain was 496.2 m3. In the total consumption of moisture, precipitation was only 34%, and the share of soil moisture was 66%.